Glycolysis mediates neuron specific histone acetylation in valproic acid-induced human excitatory neuron differentiation - Chen, Andi; Wang, Mengmeng; Xu, Chao; Zhao, Youyi; Xian, Panpan; Li, Yuqian; Zheng, Weian; Yi, Xuyang; Wu, Shengxi; Wang, Yazhou (Frontiers in Molecular Neuroscience, 2023)
Pregnancy exposure of valproic acid (VPA) is widely adopted as a model of environmental factor induced autism spectrum disorder (ASD). Increase of excitatory/inhibitory synaptic transmission ratio has been proposed as the mechanism of VPA induced ASD. How this happened, particularly at the level of excitatory neuron differentiation in human neural progenitor cells (NPCs) remains largely unclear. Here, we report that VPA exposure remarkably inhibited human NPC proliferation and induced excitatory neuronal differentiation without affecting inhibitory neurons. Following VPA treatment, mitochondrial dysfunction was observed before neuronal differentiation, as showed by ultrastructural changes, respiratory complex activity, mitochondrial membrane potential and oxidation levels. Meanwhile, extracellular acidification assay revealed an elevation of glycolysis by VPA stimulation. Interestingly, inhibiting glycolysis by 2-deoxy-d-glucose-6-phosphate (2-DG) efficiently blocked the excitatory neuronal differentiation of human NPCs induced by VPA. Furthermore, 2-DG treatment significantly compromised the VPA-induced expression of H3ac and H3K9ac, and the VPA-induced binding of H3K9ac on the promoter of Ngn2 and Mash1, two key transcription factors of excitatory neuron fate determination. These data, for the first time, demonstrated that VPA biased excitatory neuron differentiation by glycolysis-mediated histone acetylation of neuron specific transcription factors.